SANPIN RULES AND METHODS OF FOOD WASTE ANALYSIS - Махмудова D.X.; Solijonov, G.K.; Uzaydullaev, A.O.; Kuzibekov, S.K.; Jankorazov, A.M. (Eurasian Journal of Academic Research, 2023)
All developed countries of the world strive to produce waste-free products. modern technologies for processing not only household and construction waste, but also food waste are being created. The disposal of food waste is constantly being improved, creating new technologies that allow the processing of non-recyclable waste, which develops scientific work and research.